Physiological differeces between sprint and distance specialized cross-country skiiers - Losnegard, T.; Hallén, J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Sprint (</= 1,8 km) and distance skiing (>/= 15 km) performance rely heavily on the aerobic capacity. However, in sprint skiing, due to the ~ 20% higher speed (1), anaerobic capacity may contribute significantly. This study aimed to identify the possible anthropometric and physiological differences between elite male sprint and distance skiers.